The Restoration of a Wood-Frame House in Anatolia, The Yakup Aga Mansion - Erdem, Ayten; Ozakin, Rabia (TRANS TECH PUBLICATIONS LTD, 2010)
A significant part of traditional dwellings in Turkey consists of houses built with wood-frame technique. The building of wood-frame houses continued until the 1950s. Up to the 1990s, the preferred method of restoration in Turkey of wooden buildings, which have been disappearing very quickly due to many reasons, had been to demolish and to rebuild them in reinforced concrete maintaining their outside appearance. Restoration experts have constantly explained that producing copies devoid of all their original values is contrary to the spirit of preservation and nowadays the obligation to restore wooden buildings by using the method of wood-frame building has been introduced; however, despite the introduction of the wood-frame method the demolition and reconstruction of wooden buildings have continued. The Yakup Aga Mansion was built in 1911 in Gerze/Sinop The building, which was set on stone cellar walls, in three storeys with a wooden frame, is made up of two quarters. As time went by, the supporting frame weakened, leading to a partial collapse of the mansion, with the result that a project for the reconstruction of the mansion in reinforced concrete was approved, but never carried out. The mansion was expropriated in 2000 and restored in 2006. The restoration was done by paying attention to the preservation of original architectural elements, and the wood-frame was reinforced with partial renovations. In this paper, the consolidation, completion and reconstruction interventions carried out to preserve the wooden mansion will be analysed, with the aim of determining the degree of conservation of the aesthetic, historical evidence and authenticity values of the building.
Keywords: Turkey; wooden house; wood frame technique; consolidation; reconstruction; Construction & Building Technology; Engineering; Materials Science